Retail investors' contrarian behavior around news, attention, and the momentum effect - Cheng Luo; Enrichetta Ravina; Marco Sammon; Luis M. Viceira (Federal Reserve Bank of Chicago, 2023)
Using a large panel of U.S. brokerage accounts trades and positions, we show that a large fraction of retail investors trade as contrarians after large earnings surprises, especially for loser stocks, and that such contrarian trading contributes to post earnings announcement drift (PEAD) and price momentum. Indeed, when we double-sort by momentum portfolios and retail trading flows, PEAD and momentum are only present in the top two quintiles of retail trading intensity. Finer sorts confirm the results, as do sorts by firm size and institutional ownership level. We show that the investors in our sample are representative of the universe of U.S. retail traders, and that the magnitude of the phenomena we describe indicate a quantitively substantial role of retail investors in generating momentum. Alternative hypotheses, such as the disposition effect and stale limit orders, do not explain retail contrarian trading. Younger traders are more likely to be contrarian, and a firm's dividend yield, leverage, size, book to market, and analyst coverage are associated with the fraction of contrarian trades they face around earnings announcements. Attentive investors are more likely to be contrarians.
Keywords: G40; G50; G11; 330; Retail Investor; Momentum; Contrarian Trading